IFNγ-Stimulated Dendritic Cell Exosomes for Treatment of Migraine Modeled Using Spreading Depression - Pusic, Kae M.; Won, Lisa; Kraig, Richard P.; Pusic, Aya D. (Frontiers in Neuroscience, 2019)
Migraine is a common headache disorder characterized by unilateral, intense headaches. In migraine with aura, the painful headache is preceded by focal neurological symptoms that can be visual, sensory, or motor in nature. Spreading depression (the most likely cause of migraine with aura and perhaps related headache pain) results in increased neuronal excitability and related increases in inflammation and production of reactive oxygen species. This in turn can promote the transformation of low-frequency, episodic migraine into higher-frequency and eventually chronic migraine. Though migraine affects 11% of adults worldwide, with 3% experiencing chronic headache, existing therapies offer only modest benefits. Here, we focus on the mechanisms by which environmental enrichment (i.e., volitionally increased intellectual, social, and physical activity) mitigates spreading depression. In prior work, we have shown that exposure to environmental enrichment reduces susceptibility to spreading depression in rats. This protective effect is at least in part due to environmental enrichment-mediated changes in the character of serum exosomes produced by circulating immune cells. We went on to show that environmental enrichment-mimetic exosomes can be produced by stimulating dendritic cells with low levels of interferon gamma (a cytokine that is phasically increased during environmental enrichment). Interferon gamma-stimulated dendritic cell exosomes (IFNγ-DC-Exos) significantly improve myelination and reduce oxidative stress when applied to hippocampal slice cultures. Here, we propose that they may also be effective against spreading depression. We found that administration of IFNγ-DC-Exos reduced susceptibility to spreading depression in vivo and in vitro, suggesting that IFNγ-DC-Exos may be a potential therapeutic for migraine.